1981
DOI: 10.1152/ajprenal.1981.240.3.f200
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular potentials in rabbit proximal tubules perfused in vitro

Abstract: Conventional microelectrodes were used to measure the basolateral membrane potential (VBL) in isolated perfused superficial proximal convoluted (sPCT) and superficial proximal straight (sPST) tubules of the rabbit kidney. Stable recordings for periods up to 2 h can be obtained. The mean +/- SE (n = number of cells) values of VBL were sPCT = -51.0 +/- 1.63 (24) and sPST = -47.0 +/- 0.97 (94) mV. Inhibitors of active transport, ouabain (10(-5) M) and low bath potassium (0.1 mM), caused a significant depolarizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
3

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 0 publications
4
41
3
Order By: Relevance
“…ability or basolateral membrane PD). In this regard, interesting to compare the first and fourth Biagi et al (40) have observed recently that peritui Fig. 4.…”
Section: Methodsmentioning
confidence: 89%
“…ability or basolateral membrane PD). In this regard, interesting to compare the first and fourth Biagi et al (40) have observed recently that peritui Fig. 4.…”
Section: Methodsmentioning
confidence: 89%
“…The luminal cell membrane electrogenic proton pump should be affected by the electrical potential across the apical cell membrane, while the basolateral cell membrane Cl-HCO3 exchanger should be insensitive to the voltage across the basolateral cell membrane but sensitive to the relative concentrations of Cl and HCO3 across this membrane. Since elevation of peritubular K concentration to 50 mM in proximal convoluted and proximal straight tubule cells as well as CCT cells results in major depolarization of intracellular voltage (10,11,14), we would expect to observe an effect on net HCO3 absorption if the basolateral cell membrane of the MCD cell also possessed high K conductance. Thus, if elevation of the peritubular K concentration to 50 mM significantly depolarizes the cell, one would expect an increase in proton secretion due to improvement of the electrical gradient against which the proton pump must work.…”
Section: Discussionmentioning
confidence: 99%
“…In the first protocol, we examined the effect of depolarizing the basolateral membrane on J, and PD. During the experimental period, 2 mM BaC12, a potassium conductance inhibitor (12)(13)(14), was added to the bathing media. In the second protocol, we examined the effect of anthracene-9-CO2H, a presumptive Cl-conductance inhibitor (16)(17)(18), on J, and PD.…”
Section: Methodsmentioning
confidence: 99%
“…protocol the effect of depolarizing the basolateral membrane with Ba"+ on NaCi transport was examined (12)(13)(14)(15). Depolarizing the basolateral membrane would decrease the electrical driving force for conductive Cl-exit and inhibit NaCl transport if Cl-exit were conductive.…”
Section: Introductionmentioning
confidence: 99%